Question
upstudy study bank question image url

\( \begin{array}{lll}y-2 x=2 & \text { and } & x^{2}-2 x=3-y \\ y=-x-3 & \text { and } & y=2 x^{2}-3 x-3 \\ 3 x-y=2 & \text { and } & 3 y+9 x^{2}=4\end{array} \)

Ask by Medina Summers. in South Africa
Feb 22,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions for the systems of equations are: 1. \((x, y) = (-1, 0)\) and \((1, 4)\) 2. \((x, y) = (0, -3)\) and \((1, -4)\) 3. \((x, y) = \left(-\frac{5}{3}, -7\right)\) and \(\left(\frac{2}{3}, 0\right)\)

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y-2x=2\\x^{2}-2x=3-y\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=2+2x\\x^{2}-2x=3-y\end{array}\right.\) - step2: Substitute the value of \(y:\) \(x^{2}-2x=3-\left(2+2x\right)\) - step3: Simplify: \(x^{2}-2x=1-2x\) - step4: Cancel equal terms: \(x^{2}=1\) - step5: Simplify the expression: \(x=\pm \sqrt{1}\) - step6: Simplify: \(x=\pm 1\) - step7: Separate into possible cases: \(x=1\cup x=-1\) - step8: Rearrange the terms: \(\left\{ \begin{array}{l}x=1\\y=2+2x\end{array}\right.\cup \left\{ \begin{array}{l}x=-1\\y=2+2x\end{array}\right.\) - step9: Calculate: \(\left\{ \begin{array}{l}x=1\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=-1\\y=0\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=0\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=4\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=0\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=4\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(-1,0\right)\cup \left(x,y\right) = \left(1,4\right)\) Solve the system of equations \( y=-x-3; y=2 x^{2}-3 x-3 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=-x-3\\y=2x^{2}-3x-3\end{array}\right.\) - step1: Substitute the value of \(y:\) \(-x-3=2x^{2}-3x-3\) - step2: Cancel equal terms: \(-x=2x^{2}-3x\) - step3: Move the expression to the left side: \(-x-\left(2x^{2}-3x\right)=0\) - step4: Subtract the terms: \(2x-2x^{2}=0\) - step5: Factor the expression: \(2x\left(1-x\right)=0\) - step6: Separate into possible cases: \(\begin{align}&2x=0\\&1-x=0\end{align}\) - step7: Solve the equation: \(\begin{align}&x=0\\&x=1\end{align}\) - step8: Calculate: \(x=0\cup x=1\) - step9: Rearrange the terms: \(\left\{ \begin{array}{l}x=0\\y=-x-3\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-x-3\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=0\\y=-3\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-4\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=0\\y=-3\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-4\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(0,-3\right)\cup \left(x,y\right) = \left(1,-4\right)\) Solve the system of equations \( 3 x-y=2; 3 y+9 x^{2}=4 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x-y=2\\3y+9x^{2}=4\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=-2+3x\\3y+9x^{2}=4\end{array}\right.\) - step2: Substitute the value of \(y:\) \(3\left(-2+3x\right)+9x^{2}=4\) - step3: Expand the expression: \(-6+9x+9x^{2}=4\) - step4: Move the expression to the left side: \(-6+9x+9x^{2}-4=0\) - step5: Subtract the numbers: \(-10+9x+9x^{2}=0\) - step6: Factor the expression: \(\left(-2+3x\right)\left(5+3x\right)=0\) - step7: Separate into possible cases: \(\begin{align}&-2+3x=0\\&5+3x=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=\frac{2}{3}\\&x=-\frac{5}{3}\end{align}\) - step9: Calculate: \(x=\frac{2}{3}\cup x=-\frac{5}{3}\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=\frac{2}{3}\\y=-2+3x\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{3}\\y=-2+3x\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=\frac{2}{3}\\y=0\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{3}\\y=-7\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-\frac{5}{3}\\y=-7\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{3}\\y=0\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{5}{3}\\y=-7\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{3}\\y=0\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-\frac{5}{3},-7\right)\cup \left(x,y\right) = \left(\frac{2}{3},0\right)\) Here are the solutions for the given systems of equations: 1. For the system: \[ \begin{align*} y - 2x &= 2 \\ x^2 - 2x &= 3 - y \end{align*} \] The solutions are: \[ (x,y) = (-1,0) \cup (x,y) = (1,4) \] 2. For the system: \[ \begin{align*} y &= -x - 3 \\ y &= 2x^2 - 3x - 3 \end{align*} \] The solutions are: \[ (x,y) = (0,-3) \cup (x,y) = (1,-4) \] 3. For the system: \[ \begin{align*} 3x - y &= 2 \\ 3y + 9x^2 &= 4 \end{align*} \] The solutions are: \[ (x,y) = \left(-\frac{5}{3}, -7\right) \cup (x,y) = \left(\frac{2}{3}, 0\right) \] Alternatively, in decimal form: \[ (x,y) = (-1.6, -7) \cup (x,y) = (0.6, 0) \] These results provide the pairs \((x,y)\) that satisfy each respective system of equations.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Let's have some fun with these equations! For the first pair, we have a linear equation and a modified quadratic equation. Solving the first pair, \( y - 2x = 2 \) can be rewritten as \( y = 2x + 2 \). Substituting this into \( x^2 - 2x = 3 - y \), we get a quadratic equation that we can solve for \( x \) and then plug back to find \( y \). Moving on to the second set of equations where \( y = -x - 3 \) meets the quadratic equation \( y = 2x^2 - 3x - 3 \). Here, we can set them equal to find points of intersection. Ultimately, we’re looking to find that sweet spot where both equations hold true – it’s like a dance-off for each equation! Finally, the third set introduces a mix of a linear equation alongside another polynomial. Solving \( 3x - y = 2 \) for \( y \) gives \( y = 3x - 2 \). Plugging this into the second equation results in another powerful quadratic puzzle to solve. Just remember, treat those x's and y's with care like they’re precious jewels on this mathematical adventure! Happy solving!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy